2014 Asia-Pacific Conference on Computer Aided System Engineering (APCASE) 2014
DOI: 10.1109/apcase.2014.6924467
|View full text |Cite
|
Sign up to set email alerts
|

Analysing the performance of the OpenFlow standard for software-defined networking using the OMNeT++ network simulator

Abstract: Software-defined networking (SDN) is a relatively advanced method for implementing communication networks. SDN separates the decision maker, called the control plane, which decides where packets are sent, from the underlying infrastructure, called the data plane, which forwards packets to the decided destination. A newly emerging standard for SDN is the OpenFlow standard, which includes a standardized protocol for communications between the control plane and the data plane. This study analyses the extent to wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…In summary, SDN differs from traditional networks by virtualizing the network components, giving the administrators a new level of visibility, which brings significant benefits like efficiency and agility to the network. Compared to The Open Systems Interconnection model (OSI model) (Figure 3) (Banjar et al, 2014). The OSI is a model that describes how computer systems communicate over a network using seven layers.…”
Section: Software Defined Networking (Sdn)mentioning
confidence: 99%
See 1 more Smart Citation
“…In summary, SDN differs from traditional networks by virtualizing the network components, giving the administrators a new level of visibility, which brings significant benefits like efficiency and agility to the network. Compared to The Open Systems Interconnection model (OSI model) (Figure 3) (Banjar et al, 2014). The OSI is a model that describes how computer systems communicate over a network using seven layers.…”
Section: Software Defined Networking (Sdn)mentioning
confidence: 99%
“…FIGURE 3Comparison of OSI and SDN models. Reprinted, with permission, fromBanjar et al, 2014. Copyright 2014 …”
mentioning
confidence: 99%
“…Research conducted to compare the performance of SDN with conventional networks based on the parameters of jitter, delay, and throughput showed that SDN had better delay, jitter, and throughput results (Hernandez, Jimenez, Pranolo, & Rios, 2019). In another study, it was found that, by analyzing key network metrics including round-trip-time (RTT) and data transfer rate (DTR), the results show that the location of the controller has a demonstrable effect on network performance (Banjar, Pupatwibul, Braun, & Moulton, 2014). The SDN network has Quality of Services (QoS) results compared to conventional networks and the latency value produced by SDN is between 0.019 -0.084ms (Nugroho, Irfan, & Faruq, 2019).…”
Section: Introductionmentioning
confidence: 99%